The Mid-Infrared Instrument for the James Webb Space Telescope, II: Design and Build. (4th January 2016) - Wright, G. S.; Wright, David; Goodson, G. B.; Rieke, G. H.; Aitink-Kroes, Gabby; Amiaux, J.; Aricha-Yanguas, Ana; Azzollini, Ruymán; Banks, Kimberly; Barrado-Navascues, D.; Belenguer-Davila, T.; Bloemmart, J. A. D. L.; et al.
Abstract: The Mid-InfraRed Instrument (MIRI) on the James Webb Space Telescope ( JWST ) provides measurements over the wavelength range 5 to 28.5 μm. MIRI has, within a single "package, " four key scientific functions: photometric imaging, coronagraphy, single-source low-spectral resolving power (R ∼ 100) spectroscopy, and medium-resolving power (R ∼ 1500 to 3500) integral field spectroscopy. An associated cooler system maintains MIRI at its operating temperature of < 6.7 K. This paper describes the driving principles behind the design of MIRI, the primary design parameters, and their realization in terms of the "as-built" instrument. It also describes the test program that led to delivery of the tested and calibrated Flight Model to NASA in 2012, and the confirmation after delivery of the key interface requirements.